Thermophilic Xylanase Production Rom Isolates of Macula’ Hot Springs Bacteria Using Corn Cobs Waste Media - Lupita Denta Putri; Hasnah Natsir; Seniwati Dali (Hasanuddin University, 2017)
Xylanases is an extracellular enzyme that has prospects as enzymes that hydrolyze hemicellulose (xylan). In this study, carried out isolatied of bacteria from the hot springs Makula', Tana Toraja and determine the optimum conditions in producing the xylanase enzyme. The steps being taken are the rejuvenation of bacteria, the manufacture medium inoculum and the production medium, the measurement OD (Optical Density) measurements of protein and testing activities xylanase. The results obtained showed that the production time for B. stearothermophilus SL3A is in the 48 hours with a value of 0.1237 activity mU/mL and B. stearothermophilus SL3S at the 60 hours with a value of 0.1593 activity mU/mL. B. stearothermophilus SL3A have a protein content of 9.828 mg/mL and for B. stearothermophilus SL3S have a protein content of 10.07 mg/mL. Characteristics bacterial xylanase from B. stearothermophilus SL3A and B. stearothermophilus SL3S work optimally at pH 7 a temperature of 45 ºC. Crude extract of the isolated xylanase enzyme can hydrolyze substrate is xylan corn cobs. The addition of metal CaCl2, MgCl2, CaCl2 can increase the activities of the enzyme xylanase and CoCl2 decreases the activities of enzymes that are inhibitors.